2021
DOI: 10.2991/ahsr.k.210115.011
|View full text |Cite
|
Sign up to set email alerts
|

High Proportion of Vitamin D Deficiency in Male Adolescents in Yogyakarta Indonesia

Abstract: Deficiency of vitamin D in the world is high. Vitamin D deficiency has numerous negative effects. The purpose of this study was to determine the proportion of vitamin D deficiency in male adolescents in Yogyakarta Indonesia. This research is a cross-sectional study. The height, weight, physical activity, lipid profile laboratory data and vitamin D levels of subjects were recorded in the study. Body mass index (BMI) is calculated as body weight divided by height. Moderate exercise in physical is determined as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In the study from Judistiani et al in 2019, it was shown that of 203 pregnant women at the Gynecology Polyclinic, Dr. Hasan Sadikin Hospital, Bandung, West Java, also suffered from deficient levels of vitamin D at a rate as high as 75% [24]. In the study from Arjana et al in 2021, in the group of adolescents in Yogyakarta, as many as 26 (43.3%) people showed a deficient level of Vitamin D, and 31 (51.7%) people showed an insufficient level of Vitamin D [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the study from Judistiani et al in 2019, it was shown that of 203 pregnant women at the Gynecology Polyclinic, Dr. Hasan Sadikin Hospital, Bandung, West Java, also suffered from deficient levels of vitamin D at a rate as high as 75% [24]. In the study from Arjana et al in 2021, in the group of adolescents in Yogyakarta, as many as 26 (43.3%) people showed a deficient level of Vitamin D, and 31 (51.7%) people showed an insufficient level of Vitamin D [25].…”
Section: Discussionmentioning
confidence: 99%
“…Sharan and team [11] on women and men aged 55-65 years. In North Sumatra, however, Keumala [14] found that 95% of adult women had vitamin D deficiency and insufficiency. Arjana's team [15] in Yogyakarta found that in adult males aged 19-25 years, the proportion of deficiency of vitamin D was 43.3%, Mahmodnia's team [20] reported a strong positive correlation of vitamin D and age.…”
Section: Discussionmentioning
confidence: 99%
“…The average vitamin D intake recommended by the Institute of Medicine (IOM) for females and males aged 18-70 years is 15 μg/day[19]. Vitamin D-containing foods are among others egg yolk, salmon, mackerel, tuna, meat, mushrooms, cod liver oil, and fortified foods[14,19]. According to the study of Masood and Iqbal, as cited by Keumala et al[14] the inability to buy vitamin D-containing foods results in the occurrence of vitamin D deficiency.…”
mentioning
confidence: 99%
“…27 Another study conducted on men in Yogyakarta, Indonesia, also showed that the proportion of vitamin D deficiency and insufficiency was relatively high but was not significantly associated with obesity, lipid profile, and physical activity. 11 Several studies have found low 25(OH)D levels in women with high body fatness and normal and low body fatness subjects. 27,28 This shows that several other factors, apart from body fat composition, can cause subjects with high or normal body fat to experience vitamin D deficiency.…”
Section: Analysis Of Vitamin D Levels In the Obese And Non-obese Groupsmentioning
confidence: 99%
“…8,9 Vitamin D deficiency often occurs not only in countries with four seasons with limited sun exposure, but currently, vitamin D deficiency is also reported to occur in tropical countries with excellent, year-round sun exposure, including Indonesia. [10][11][12] Based on the literature search, no study has examined the comparison of vitamin D levels in obese and non-obese subjects in Indonesia's population of health workers. Vitamin D deficiency in health workers increases the risk of being infected with COVID-19, so they need special attention.…”
Section: Introductionmentioning
confidence: 99%